Modernization Processes of the Russian Society - V. L. Kurabtsev (Vestnik MGIMO-Universiteta)
In the article features of the relations between such reality traditions and innovations in the aspect of modernization processes of the Russian society. The interrelation and the interdependence of these notions and spiritual traditions of Russian ethnos, as the main factors of counteraction to the destructive processes of social existence are defined. Spiritual traditions represent the mechanism of self-defense, self-organization and modifications of the society as a whole, so it can be regarded as the mechanism of succession and renovation. The article also indicates the necessity of radical rethinking of accepted values of modern civilization.